Fat embolism syndrome before surgical treatment of open tibial and fibular shaft fracture: a case report - Khalil, Kareem S.; Ibrahim, Samah A.; Yakout , Nada A. (International Journal of Research in Orthopaedics, 2025)
A 26-year-old male with no significant medical history sustained open fractures of the left tibia and fibula following a workplace accident. Initially alert and stable, he developed sudden neurological deterioration (GCS 9/15) 10 hours post-injury, without respiratory compromise or cutaneous signs. CT was unremarkable; diffusion-weighted MRI revealed widespread acute cerebral infarcts. No intracardiac shunt was found on echocardiography. Supportive care led to gradual neurological improvement, and successful surgical fixation followed. Isolated cerebral fat embolism can precede orthopedic intervention and present without classic signs. Early neuroimaging and high clinical vigilance are crucial for prompt diagnosis and management.